Kritik Terhadap Sistem Kerja dan Pola Hidup Kapitalistik Masyarakat Modern dalam Pengkhotbah 3:1-15: Studi Interdisipliner - Satya Sawung Wirayudha; Rika Amelia Br. Pardede; Sulistiono (Student Evangelical Journal Aiming At Theological Interpretation, 2026)
This study aims to analyze Ecclesiastes 3:1–15 as a structural theological critique against the labor system and capitalistic lifestyle of modern society. This qualitative research applies an interdisciplinary hermeneutical approach. The analytical procedure is carried out systematically through four operational stages: textual-philological exegesis of the Masoretic text, theological contextualization (Fides Quaerens Intellectum), integration of social theology, and dialectical synthesis with critical sociology and contemporary philosophy. The findings indicate a fundamental clash between divine temporality, which is cyclic and organic, and capitalistic temporality, which is linear and instrumental. Through the concepts of time (‘et), eternity (‘olam), and justice for the pursued (nirdāp), this ancient text radically deconstructs modern pathologies such as social acceleration, labor alienation, time commodification, and the burnout epidemic institutionalized by neoliberal market structures. This study concludes that the concept of time in Ecclesiastes 3:1–15 functions as a theological-political manifesto that rejects the reduction of human ontological dignity to a mere economic commodity. Consequently, churches, particularly in Indonesia, are called to correct prosperity theology and develop a humanist, prophetic, and transformative social praxis.